Discovery of New Chaotic Systems: Based on Existing Systems - Cigal, Tuncay; Tanyildizi, Erkan (Institute of Electrical and Electronics Engineers Inc., 2024)
Chaotic systems have been an important area of focus for researchers in science and engineering because they reflect the complexity and uncertainty of nature. The discovery of new chaotic systems is an important step towards a better understanding and control of the real world. This work aims to construct new chaotic systems based on existing chaotic systems and makes an important contribution to this field. The developed method has been successfully validated on one-dimensional chaotic systems. Detailed analysis of the generated chaotic systems shows that they effectively fulfill the basic requirements of chaotic properties. These findings suggest that this new approach may have significant potential in many practical applications in the future. © 2024 IEEE.
12th International Symposium on Digital Forensics and Security, ISDFS 2024 -- 29 April 2024 through 30 April 2024 -- San Antonio -- 199532
Keywords: bifurcation diagram; chaos; chaotic map; Lyapunov exponent